The Origin of Religion in Ancient Egypt and Information About IT - Kholmirzayeva, Setora (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the origins of the ancient Egyptian people, their religious beliefs, and the views of scholars on their early religion. This article gives you a brief overview on the religious beliefs of the Egyptians. The first study of the Egyptian religion is also described